Incidence of Positive Venereal Disease Research Laboratory (VDRL) in Patients Attended at the São José dos Campos Clinical Analysis Laboratory, in the State of São Paulo (SP) (Research, Society and Development, 2023)
This study aimed to identify the frequency of positive VDRL in individuals treated at a clinical analysis laboratory in the city of São José dos Campos/SP, considering age group, gender and pregnant women, in addition to determining which group had a higher incidence of positive VDRL. A cross-sectional study was carried out using the database of a clinical analysis laboratory in São José dos Campos, in which 3,427 laboratory reports were analyzed between April 2022 and April 2023. Before the start of the research, the work was submitted and approved by the Research Ethics Committee of Universidade Paulista, under opinion number 68294523.4.0000.5512. The study revealed a 4.26% rate of reactive VDRL tests, with the disease being higher among men, with a rate of 8.24%, compared to the incidence rate of 2.87% in the female group. women. The age group with the highest incidence was 21 to 29 years old, with 36.99% of cases, while findings in pregnant women revealed a prevalence of 2.63%, with ages between 20 and 35 years old. Therefore, it is concluded that syphilis continues to have high rates, mainly in men and individuals aged between 21 and 29 years. Therefore, the importance of sexual education, awareness and prevention programs aimed at this group is highlighted. Furthermore, syphilis in pregnant women is still a significant concern, making it necessary to reinforce prenatal care.